Optimizing the Financial Performance of Family Businesses in Indonesia: The Role of Good Corporate Governance and Sustainable Economic Growth - Putri Wahyuni (Outline Publisher, 2026)
Purpose: The purpose of this study is to examine and analyze the influence of Good Corporate Governance (GCG) and Sustainable Economic Growth (SGR) on the financial performance of family businesses in Indonesia. The research aims to understand how governance quality and sustainability-oriented growth contribute to improving profitability and long-term performance within family-owned enterprises. Methods: This study employs a quantitative research approach using multiple linear regression analysis. The data were collected from 65 family businesses listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. Results: The analysis reveals that GCG has a positive and significant effect on financial performance, demonstrating that effective governance enhances company efficiency and profitability. Similarly, SGR also significantly influences financial performance, suggesting that sustainable economic practices-integrating social and environmental considerations-contribute to long-term business success. Together, GCG and SGR explain 50.7% of the variation in the financial performance of family businesses, indicating a strong combined influence of governance and sustainability factors. Conclusions: The findings emphasize the importance of implementing Good Corporate Governance and sustainability-oriented growth strategies in family businesses to ensure both financial success and long-term viability. Originality/value: This study provides new empirical evidence on the dual role of GCG and sustainable economic growth in shaping the financial performance of family businesses in Indonesia-a sector that plays a central role in national economic development. The research contributes to the literature by combining governance and sustainability perspectives, offering insights for business owners, investors, and policymakers in promoting responsible and sustainable family business management.